Mycophenolate Mofetil Versus Cyclophosphamide for Remission Induction in Childhood Polyarteritis Nodosa: An Open‐Label, Randomized, Bayesian Noninferiority Trial. Issue 9 (31st July 2021) - Brogan, Paul A.; Arch, Barbara; Hickey, Helen; Anton, Jordi; Iglesias, Este; Baildam, Eileen; Mahmood, Kamran; Cleary, Gavin; Moraitis, Elena; Papadopoulou, Charalampia; Beresford, Michael W.; Riley, Phil; et al.
Abstract : Objective: Cyclophosphamide (CYC) is used in clinical practice off‐label for the induction of remission in childhood polyarteritis nodosa (PAN). Mycophenolate mofetil (MMF) might offer a less toxic alternative. This study was undertaken to explore the relative effectiveness of CYC and MMF treatment in a randomized controlled trial (RCT). Methods: This was an international, open‐label, Bayesian RCT to investigate the relative effectiveness of CYC and MMF for remission induction in childhood PAN. Eleven patients with newly diagnosed childhood PAN were randomized (1:1) to receive MMF or intravenous CYC; all patients received the same glucocorticoid regimen. The primary end point was remission within 6 months while compliant with glucocorticoid taper. Bayesian distributions for remission rates were established a priori for MMF and CYC by experienced clinicians and updated to posterior distributions on trial completion. Results: Baseline disease activity and features were similar between the 2 treatment groups. The primary end point was met in 4 of 6 patients (67%) in the MMF group and 4 of 5 patients (80%) in the CYC group. Time to remission was shorter in the MMF group compared to the CYC group (median 7.1 weeks versus 17.6 weeks). No relapses occurred in either group within 18 months. Two serious infections were found to be likely linked to MMF treatment. Physical and psychosocial quality‐of‐life scores were superior in the MMF group compared to the CYC group at 6 months and 18 months. Combining the prior expert opinion with results from the present study provided posterior estimates of remission of 71% for MMF (90% credibility interval [90% CrI] 51, 83) and 75% for CYC (90% CrI 57, 86). Conclusion: The present results, taken together with prior opinion, indicate that rates of remission induction in childhood PAN are similar with MMF treatment and CYC treatment, and MMF treatment might be associated with better health‐related quality of life than CYC treatment.